2016
DOI: 10.1055/s-0042-106904
|View full text |Cite
|
Sign up to set email alerts
|

Squarrosine A and Pyrrolhuperzine A, New Lycopodium Alkaloids from Thai and Philippine Huperzia squarrosa

Abstract: Two new Lycopodium alkaloids, squarrosine A (1) and pyrrolhuperzine A (2), were isolated from the Thai and Philippine plant Huperzia squarrosa. (R)-2-Piperidineacetic acid (5) was a known alkaloid, but has now been isolated for the first time from a natural source. Their structures were elucidated using extensive spectroscopic analyses and, for pyrrolhuperzine A (2), confirmation by chemical transformation. The new compounds exhibited moderate acetylcholinesterase inhibitory activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…As no differences were observed in retention time and in fragmentation pattern (Figure ), it could be concluded that the samples actually contained the esters of homopipecolic acid and homoproline. Homopipecolic acid was described before in Lycopodium species as an intermediate of the synthesis of Lycopodium alkaloids, while homoproline was isolated from Asteraceae species, as a precursor of pyrrolizidines, but their co‐occurrence has never been reported in plants and their biosynthetic origin is not known.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As no differences were observed in retention time and in fragmentation pattern (Figure ), it could be concluded that the samples actually contained the esters of homopipecolic acid and homoproline. Homopipecolic acid was described before in Lycopodium species as an intermediate of the synthesis of Lycopodium alkaloids, while homoproline was isolated from Asteraceae species, as a precursor of pyrrolizidines, but their co‐occurrence has never been reported in plants and their biosynthetic origin is not known.…”
Section: Resultsmentioning
confidence: 99%
“…Homopipecolic acid was described before in Lycopodium species as an intermediate of the synthesis of Lycopodium alkaloids, 41,42 while homoproline was isolated from Asteraceae species, as a precursor of pyrrolizidines, 40 but their co-occurrence has never been reported in plants and their biosynthetic origin is not known.…”
Section: Identification Of Beta Amino Acid Derivativesmentioning
confidence: 99%
“…Such an asymmetric transformation could efficiently address the intrinsic challenges of the classic intramolecular Schmidt reaction, [10] including the use of azides with low nucleophilicity as a substrate, the general requirement for stoichiometric amounts of a strong Lewis or Brønsted acid to activate the carbonyl group of the other reactant, the relatively strong Lewis basic nature of the resulting lactam, and the lack of the corresponding catalytic asymmetric fashion. Notably, the resulting chiral bicyclic lactams could be used as the key precursors for the total synthesis of various bioactive alkaloids, such as cephalotaxine, [4b] squarrosine A, [4c] and fluvirosaone B [4d] . Herein, we report a novel copper‐nitrene‐catalyzed asymmetric intramolecular tandem oxaziridination/rearrangement reaction to produce a chiral fused bicyclic lactam.…”
Section: Methodsmentioning
confidence: 99%
“…Löve & D. Löve (Huperziaceae) is an epiphytic clubmoss mainly distributed in Southeast Asia, Oceania, and Southwest China that can be found on trees and rocks in lowland to mid-altitude forests . The first study on the alkaloidal constituents of this plant was reported in 2011; since then, dozens of Lycopodium alkaloids with diverse structures have been isolated. As part of our ongoing search for structurally intriguing and biologically significant alkaloids, , the aerial parts of P. squarrosus collected from Guangxi Zhuang Autonomous Region of China were studied. This investigation led to the isolation of 18 new Lycopodium alkaloids, namely, eight lycopodine-type ( 1 – 8 ), seven lycodine-type ( 9 – 15 ), two fawcettimine-type ( 16 and 17 ), and a miscellaneous alkaloid ( 18 ), as well as eight known alkaloids.…”
mentioning
confidence: 99%